Impact of delivery method on the efficacy of biological control agents and the virulence of Fusarium root rot pathogens in the greenhouse. Issue 12 (2nd December 2018) - Parikh, L.; Adesemoye, A.O.
ABSTRACT: Biological control methods are now more valuable as a plant disease management strategy and are a particularly promising method for managing fusarium root rot, an economically important soilborne disease of row crops. Currently, the management of the disease relies on fungicide seed treatment, but a better understanding of disease development by fusarium root rot pathogens is crucial to enable the better utilisation of biological control agents (BCAs) or biological products. The BCA application method is a very important factor that affects efficacy. This study aimed to (i) identify the inoculation method that leads to appropriate inoculum level and reliable disease development in the greenhouse for fusarium root rot pathogens in corn, soybean, and wheat and (ii) evaluate different application methods for biocontrol agents to determine the most consistent method for enhancing the efficacy of biocontrol agents and products. Greenhouse studies were conducted in a randomised complete block design and the experiments were repeated. Disease severity was significantly high and consistent in the greenhouse when pathogens were inoculated through millet inoculation or agar plug inoculation methods. The pathogen dose rate did not affect disease development. The performance and efficacy of BCAs against fusarium root rot in soybean, corn, and wheat were highest when a combination of coating by seed spray and drenching was the method of application.